2020
DOI: 10.1097/gox.0000000000003112
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Flap-based Breast Reconstruction versus Abdominoplasty: The Impact of Surgical Procedure on Scar Location

Abstract: Background: Autologous breast reconstruction has been demonstrated to be associated with superior patient-reported outcomes, and hence is regarded as the gold standard reconstructive modality. A common drawback of this procedure, however, is related to a high abdominal scar. Recently, hybrid breast reconstruction (ie, the combination of autologous and implant-based reconstruction) was presented as an approach that would combine the benefits of both reconstructive modalities. In this study, we sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…This difference could be explained by the challenge of the DIEP flap procedure, where sufficient abdominal soft tissue is needed to create the volume for the reconstructed breast(s) while respecting underlying perforator anatomy. DIEP flap donor site closure can result in a more tighter and higher scar location than an abdominoplasty [24]. In the absence of data into scarring after BR, we found that women in our study population appraised their breast scars similar to women who had undergone a breast augmentation [25] and better than women after a reduction mammoplasty [26].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This difference could be explained by the challenge of the DIEP flap procedure, where sufficient abdominal soft tissue is needed to create the volume for the reconstructed breast(s) while respecting underlying perforator anatomy. DIEP flap donor site closure can result in a more tighter and higher scar location than an abdominoplasty [24]. In the absence of data into scarring after BR, we found that women in our study population appraised their breast scars similar to women who had undergone a breast augmentation [25] and better than women after a reduction mammoplasty [26].…”
Section: Discussionmentioning
confidence: 71%
“…However, in these studies, women after DIEP flap reconstruction were not included. Although one of the main appeals for women opting for a DIEP flap BR is the possibility of an 'abdominoplasty' like improvement of their abdomen [4,24], it is plausible that women who wish to have BR are primarily focused on restoring the breast, instead of a additional consequence such as the large abdominal scar. The worse scar appraisal of the abdomen could be explained by the dissatisfaction with the size and noticeability of this scar, which women in our study rated significantly worse than the breast scar.…”
Section: Discussionmentioning
confidence: 99%
“…Auch wird durch die Hebung der Lappenplastik nicht nur der infraumbilikale Haut-/Weichteilüberschuss korrigiert, sondern es resultiert auch die Möglichkeit einer, im Vergleich zur konventionellen autologen Brustrekonstruktion, tieferen Narbenplatzierung. Es ist erwähnenswert, dass diese tiefere Narbenlokalisation mit einer besseren ästhetischen Beurteilung einhergeht 14…”
Section: Hybridrekonstruktionunclassified
“…Das rekonstruktive Ziel nach Mastektomie ist eine Brust von adäquater Größe und Form, welche symmetrisch, weich und sensibel ist ("5 S": size, shape, symmetry, softness, sensation) [14]. Selbstverständlich sollte das gewählte Verfahren sicher ("safe") sein, so dass auch von den "6 S" gesprochen werden könnte.…”
Section: Introductionunclassified
See 1 more Smart Citation